Investigation of terahertz optical wireless communication systems - Shen, Xiao Ze (2015)
Over the past few years, the demand of wireless communication systems have drastically increased due to today’s new life style. A much higher speed wireless communication is the urgent demand for everyone. In recent years, free space optical (FSO) communications systems as well as terahertz communication systems have a trend to stand out among the other wireless communication technologies. It is regard as a key wireless communication technology to satisfy this demand. The THz region of the electromagnetic spectrum is from about 100 GHz to 10 THz and it is expected to provide greater communications bandwidth than is available at microwave frequencies. However, it still has a lot of challenges to use it because the lack of practical technologies for generating and detecting the radiation which is known as “THz gap”. Much effort is focused on the development of efficient sources, sensitive detectors, and suitable modulators in this range. The Terahertz optical communication system is a subset of FSO communication system which can deliver us to an age of much wider bandwidth, small signal attenuation and low financial cost. Both of the systems are working according to the same theory. So fully understand the FSO system is the best the best way to investigate the Terahertz communications. This report focuses on FSO communication systems for future investigation of THz communications. A FSO communication link is built by the optisystem software in the laboratory. The whole system consists of a transmitter, a FSO channel, a low pass Bessel filter and a receiver with power meters and a BER analyzer at the end. And the report investigates the performance of FSO communication systems at different optical powers of the transmitter, FSO channel attenuations, signal wavelengths, beam divergences in the laser of the FSO channel, signal formats (NRZ and RZ) and receiver aperture diameters of the FSO channel. The results are recorded and listed in the tables. The relations of BER between each parameters in this system are plotted into diagrams to analysis. By analysis all these properties of FSO system, the report gives some recommendations and expectations to the future development of THz optical wireless communication systems.